Examination of Students’ Record Management Practices in National Open University of Nigeria (NOUN) - Vivian Ailakhu Ugonna; Abdulsalam Afolabi (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study examines the record management practices in National Open University of Nigeria (NOUN). In recent years, the effective management of student records has become increasingly critical in Open and Distance Learning institutions (ODL) due to the complex nature of distance education, involving large numbers of students, multiple learning platforms, and diverse administrative processes. Data was collected through surveys with staff involved in record management at NOUN. The findings revealed while records management practices within the Directorate of Academic Registry are relatively strong, enhancements in storage capacity, environmental controls, and stricter safety regulations could further optimise efficiency. The study recommended the university management to constantly upgrade the recommended records management systems with extensive server capabilities to meet the needs of all students and other users and to enhance policies to ensure the accuracy, accessibility, and security of student records.